Um estudo a respeito do existencial compreensão na obra Ser e Tempo de Martin Heidegger - Bueno, Ricardo Radin (2012)
This paper intends to discuss about the existential understanding in the work Being and Time by Martin Heidegger. This should be donne having in sight Dasein as it was conceptualized by the author as having a fundamental relationship with his own existence in the world, this determining its essence. Thus, the existential understanding participates of the triumvirate: state-of-mind, understanding and language, that define the being-there in its opening. Focusing on understanding the meaning of being, determining the daily life od Dasein, the work evolves as described below. In the first chapter, something is said about the time of study of Heidegger that preceded the writing of Being and Time. In the second chapter, something is said about Husserl and the particular impact that his ideas had in heideggerian thought, often build as a possible response to them. In the third chapter, the work Being and Time is clearly thematized, and something is said about its structure, especially in the characteristics of Dasein which refers to being-in-the-world, everyday being, understanding and interpretation. In the fourth chapter something is said about the consequences of Heidegger s hermeneutics as presented, with regard to what Heidegger presents as unique in the understanding of being of Dasein